IMPLEMENTASI EVALUASI PEMBELAJARAN BERBASIS KOMPETENSI UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH MENENGAH PERTAMA - Dwi Feriwanti; Hendro Prasetyono (STKIP Subang, 2025)
Competency-based learning evaluation is one of the key factors in improving junior high school students' learning outcomes. This study aims to analyze the implementation of competency-based learning evaluation and its impact on student learning outcomes at junior high schools. This research uses a quantitative descriptive method with a sample of 60 fifth-grade students from two junior high schools in Central Jakarta . Data were collected through observation, tests, and documentation. The results showed that the implementation of competency-based learning evaluation covering three domains (cognitive, affective, and psychomotor) significantly improved student learning outcomes. The average increase in learning outcomes reached 25.3% after the implementation of competency-based evaluation. This research concludes that competency-based evaluation that is conducted systematically and comprehensively can effectively improve junior high school students' learning outcomes.